Synthesis and biological evaluation of novel marine-derived indole-based 1, 2, 4-oxadiazoles derivatives as multifunctional neuroprotective agents. Issue 2 (15th January 2015) - Jiang, Cheng-Shi; Fu, Yan; Zhang, Li; Gong, Jing-Xu; Wang, Zhen-Zhong; Xiao, Wei; Zhang, Hai-Yan; Guo, Yue-Wei
Graphical abstract